Қазақстандағы зерттеу этикасының пайда болуы мен дамуы: Көшпелілердің моральдық философиясы халықаралық зерттеу этикасымен байланысты ма? - Zhakupova, A. D.; Sharplin, E.; Ismagulova, A. E.; Rakisheva, G. M.; Ramazanova, M. R.; Abildina, R. Z. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2022)
The article examines the influence of the traditional culture of the Kazakh people and Western ethical theories on the development of research ethics in modern Kazakhstan. A review of Western ethical theories and ethical traditions of Turkic nomads made it possible to identify the correspondence of the principles of modern Western research ethics with the ethical principles and values of traditional Kazakh culture. The authors explored connections between modern research ethics and early ethical thinking of Kazakhs through the theory of principlism, based on the principles of respect for autonomy, beneficence, non-maleficence, and justice. All the principles of Western ethics are embodied in traditional Kazakh culture, historically established as national values. The principle of autonomy occupies a special place due to its own national and cultural specifics and it, to a certain extent, is opposed to international standards. The article emphasizes the importance of supporting ethical research in the context of the globalization of education in Kazakhstan. This study was financed by Nazarbayev University Collaborative Research Grant №021220CRP0922 for which the authors are grateful. Key words: ethics, research, culture, globalization, traditions, philosophy of nomads, morality.